Clinicopathologic characteristics, diagnostic clues, and prognoses of patients with multiple sporadic gastrointestinal stromal tumors: a case series and review of the literature - Yan-Ying Shen; Xin-Li Ma; Lin-Xi Yang; Wen-Yi Zhao; Lin Tu; Chun Zhuang; Bo Ni; Qiang Liu; Ming Wang; Hui Cao (BMC, 2020)
Abstract Background Most sporadic gastrointestinal stromal tumors (GISTs) occur as solitary tumors, while multiple sporadic GISTs are extremely rare and often misdiagnosed as metastatic GISTs, leading to inappropriate treatment. This study aimed to investigate the clinicopathological characteristics, diagnostic clues, and prognoses of multiple sporadic GISTs. Methods Twenty-seven patients with multiple sporadic GISTs and 11 patients with metastatic GISTs mimicking sporadic GISTs were analyzed. The clinicopathological characteristics, genetic mutation types, and prognoses were summarized. In addition, 1066 cases of primary GISTs with a single lesion diagnosed at the same hospital were included as controls. Results Compared with 1066 cases of primary GIST with a single lesion, multiple sporadic GISTs occurred at an older age, were more common in women than in men, and were located mainly in the stomach. They were generally small in size, had a low mitotic index and were more often rated as very low risk/low risk. Mutation analysis of all available lesions revealed different KIT/PDGFRA mutation patterns among tumors from the same patients. No patient relapsed during the follow-up period. Among 11 patients with metastatic GISTs that mimicked multiple sporadic GISTs, multiple lesions from the same patient always had concordant pathological and mutational characteristics; namely, they carried an identical KIT/PDGFRA mutation, and the mitotic index was usually high. Conclusions The prognoses of patients with multiple sporadic GISTs were not worse than those of patients with a single lesion of the same risk under the same treatment. When it was difficult to distinguish multiple sporadic GISTs from metastatic GISTs, multiple lesions in the same patient carried different KIT/PDGFRA mutation patterns, which supported tumor multiplicity, while the concordant hypermitotic phase in multiple lesions of GISTs suggested that the tumor was metastatic.